BUSINESS MODEL CANVAS AND SWOT ANALYSIS IN THE RECONSTRUCTION OF COMPETITIVE STRATEGY: A CASE STUDY VCI INDONESIA COMPANY (Malaysian Management Journal, 2023)
This study aims to develop an advanced business model canvas (BMC) by incorporating the results of a SWOT analysis in the contextof VCI Indonesia Company. The research focuses on understanding the competitive strategy of VCI Indonesia Company, particularlythose that emphasize natural ingredients and target specific consumer segments. To achieve this, interviews were conducted to gather insights related to the nine pillars of BMC and SWOT analysis from VCI Indonesia Company. The collected data was then analyzed, resulting in the compilation of BMC and SWOT analysis tables. The findings of the study highlight the competitive advantages of VCI Indonesia Company in utilizing natural ingredients and their potential for expanding and implementing new marketing strategies. By incorporating the SWOT analysis results into an enhanced BMC model, this research introduces a novel competitive strategy that can ensure the company’s sustainability and adaptability to changes in the market. Notably, this study is unique in its focus on the business strategy of natural body care product companies, offering valuable insights from the consumer’s perspective that have not been extensively explored in previous research. The practical implication of this research lies in providing business recommendations based on consumer preferences and market competition for companies that sell natural products.